Production of cellulase and laccase enzymes by Oudemansiella radicata using agro wastes under solid-state and submerged conditions - Balaraju, K.; Park, Kyungseok; Jahagirdar, Shamarao; Kaviyarasan, V. (Research in Biotechnology, 2010)
Oudemansiella radicata (Relhan ex Fr.) is one of the medicinally important edible mushrooms belonging to Tricholomataceae. In the present study we reported the efficient production of cellulase and laccase enzymes by O. radicata under submerged (SMF) and solid-state (SSF) fermentations. O. radicata had grown well both in submerged and solid-state conditions. Under submerged condition the maximum cellulase activity (490 units / ml / min) was observed. In the case of SSF the maximum cellulase activity was observed as 400 units / ml / min in wheat bran, followed by rice bran (367 units / ml / min). In the case of laccase production, the maximum activity was observed as 1.476 units / ml / min on 14th day at pH 7 under SMF. In solid substrate fermentation the maximum activity was noticed as 25.784 units / ml / min in rice bran. The next higher activity was 11.473 units / ml / min in wheat bran, and the least activity was recorded with saw dust. Higher levels of laccase and cellulase activity were seen in solid-state fermentation than in submerged fermentation. Hence the present results clearly explain that O. radicata is a potential candidate for the production of industrially important enzymes using agro-wastes.